EFFECT OF GRADED EXPOSURE AND TEST-TAKING SKILLS TRAINING COUNSELLING TECHNIQUES ON TEST ANXIETY AMONG SECONDARY SCHOOL STUDENTS - Adeboye, Adenike Abiola; Bello, Rahmon Ade; Sambo, Sani (Program Studi Bimbingan dan Konseling Universitas Tunas Pembangunan Surakarta, 2024)
This study investigated the effects of graded exposure and test-taking-skills training counselling techniques on test anxiety among secondary school students in Ilorin metropolis, Nigeria. The study employs a quasi-experimental pre-test/post-test design involving SS2 students identified with high test anxiety. The study measured anxiety levels before and after a 6-week graded exposure treatment programme and test-taking skills training treatment. Data was analysed using paired sample t-tests to compare pre-test and post-test scores. The findings of this study revealed that graded exposure counselling technique had a significant effect on physiological (t = 20.38, p = 0.000), cognitive (t = 20.70, p = 0.000), behavioural (t = 20.73, p = 0.000) and emotional (t = 11.81, p = 0.000) components of test anxiety among secondary school students in Ilorin metropolis. It was also revealed that test-taking skills training counselling technique had a significant effect on physiological (t = 20.68, p = 0.000), cognitive (t = 16.61, p = 0.000), behavioural (t = 16.55, p = 0.000) and emotional (t = 19.23, p = 0.000) components of test anxiety among secondary school students in Ilorin metropolis. It was recommended among others that, Professional Counsellors and Psychologists should include the use of graded exposure and test-taking skills training techniques in the secondary school programmes and training to assist students in learning how to face their related test anxiety in a gradual process and overcome them.